Crash and Impact Analysis of Light Vehicle Against Traffic Light Pole - Raguraman, Puvanithan; Ibrahim, Mohd Norihan (Research Progress in Mechanical and Manufacturing Engineering, 2024)
When a car collides with a rigid object on the road, such as a traffic light pole or a lighting column, the occupants are put in grave danger. Collisions such as these could cause a major unfortunate to both vehicles, human and infrastructure. It will cost financially and pose harm to public or pedestrians as well.  To better understand the impact dynamics of such collisions, a study was conducted on the crash and impact analysis of a light vehicle against a traffic light pole. The study focused on the deformation of the vehicle's frontal area against the traffic light pole at various speeds, which were classified into two categories, which is medium low speed and medium high speed. The study used ANSYS explicit dynamics finite element method to conduct the numerical analysis and simulation. The total deformation, equivalent Von-Mises stress, and directional deformation analysis provided detailed insights into the dynamic response of the vehicle and traffic light pole interaction. The results shows that when going at higher speeds, the traffic light pole caused additional deformation on the frontal region of the vehicle. Due to the material quality of the aluminium alloy, the car absorbed more impact energy than the traffic light poles due to the high internal energy released during the crash. The findings of this study can help improve the safety of vehicles and traffic light poles, reducing the financial cost and harm to the public or pedestrians caused by such collisions.